RILEM recommendations for the prevention of damage by alkali-aggregate reactions in new concrete structures : state-of-the-art report of the RILEM Technical Committee 219-ACS /: state-of-the-art report of the RILEM Technical Committee 219-ACS. ([2016]) - Unknown
No abstract available